Grupos estratégicos en el sector periodístico: panorama en la ciudad de Lima - Antonio, Javier; Cornejo, Ricardo; Reinoso, Raquel; Soto, Fanny; Uribe, Sara (Universidad ESAN. ESAN Ediciones, 1995)
Describes and interprets the behavior of the national journalistic sector from the strategic groups that compete in this industry. For this, the market was segmented based on two variables: type of reader and the way of presenting the information, and a matrix of strategic groups was elaborated, according to three other variables: technology, operating leverage and specialization, to identify generic strategies developed by companies in this sector. A high correlation was found between type of information and type of reader (formal-style newspapers are aimed at traditional readers, while informal ones are aimed at "chicha" readers); having its own press as the highest mobility barrier, since this represents a significant investment for any reader company; vulnerability of all groups to substitute products; high rivalry between newspapers for some of them sharing their target markets; and leverage as the strategy of most newspapers that reach a high level of sales.

Describe e interpreta el comportamiento del sector periodístico nacional a partir de los grupos estratégicos que compiten en esta industria. Para ello, se segmentó el mercado en función de dos variables: tipo de lector y la forma de presentar la información, y se elaboró ​​una matriz de grupos estratégicos, según otras tres variables: tecnología, apalancamiento operativo y especialización, para identificar estrategias genéricas desarrolladas. por empresas de este sector. Se encontró una alta correlación entre tipo de información y tipo de lector (los periódicos de estilo formal están dirigidos a lectores tradicionales, mientras que los informales están dirigidos a lectores "chicha"); tener la prensa propia como máxima barrera a la movilidad, ya que esto representa una inversión importante para cualquier empresa lectora; vulnerabilidad de todos los grupos a productos sustitutos; alta rivalidad entre periódicos porque algunos de ellos comparten sus mercados objetivo; y el apalancamiento como estrategia de la mayoría de periódicos que alcanzan un alto nivel de ventas.
Keywords: Journalism sector; Segmentation; Sector periodismo; Business strategy; Segmentación; Estrategia empresarial; Strategic groups; Grupos estratégicos; https://purl.org/pe-repo/ocde/ford#5.02.04